PH-responsive silica nanoparticles for the treatment of skin wound infections. (June 2022) - Pan, Fei; Giovannini, Giorgia; Zhang, Sixuan; Altenried, Stefanie; Zuber, Flavia; Chen, Qian; Boesel, Luciano F.; Ren, Qun
Abstract: Chronic wounds are not only a burden for patients but also challenging for clinic treatment due to biofilm formation. Here, we utilized the phenomenon that chronic wounds possess an elevated local pH of 8.9 and developed pH-sensitive silica nanoparticles (SiNPs) to achieve a targeted drug release on alkaline wounds and optimized drug utility. Chlorhexidine (CHX), a disinfectant and antiseptic, was loaded into SiNPs as the model drug. The loaded CHX displayed a release 4 - 5 fold higher at pH 8.0 and 8.5 than at pH 6.5, 7.0 and 7.4. CHX-SiNPs furthermore exhibited a distinctive antibacterial activity at pH 8.0 and 8.5 against both Gram-negative and -positive bacterial pathogens, while no cytotoxicity was found according to cell viability analysis. The CHX-SiNPs were further formulated into alginate hydrogels to allow ease of use. The antibacterial efficacy of CHX-SiNPs was then studied with artificial wounds on ex vivo human skin. Treatment with CHX-SiNPs enabled nearly a 4-lg reduction of the viable bacterial cells, and the alginate formulated CHX-SiNPs led to almost a 3-lg reduction compared to the negative controls. The obtained results demonstrated that CHX-SiNPs are capable of efficient pH-triggered drug release, leading to high antibacterial efficacy. Moreover, CHX-SiNPs enlighten clinic potential towards the treatment of chronic wound infections. Statement of significance: A platform for controlled drug release at a relatively high pH value i.e., over 8, was established by tuning the physical structures of silica nanoparticles (SiNPs). Incorporation of chlorhexidine, an antimicrobial agent, into the fabricated SiNPs allowed a distinctive inhibition of bacterial growth at alkaline pHs, but not at acidic pHs. The efficacy of the SiNPs loaded with chlorhexidine in treating wound infections was further validated by utilizing ex vivo human skin samples. The presented work demonstrates clinic potential of employing alkaline pH as a non-invasive stimulus to achieve on-demand delivery of antimicrobials through SiNPs, showcasing a valuable approach to treating bacterial infections on chronic wounds. Graphical abstract: Image, graphical abstract